Consolidation of material and waste management parameters for development of sustainable building rating systems - Mohammed Usman, Abdullahi; Abdullah, Kamil (Zes Rokman Resources, 2014)
Material and waste are important categories as they constitute of more than 60% of the project cost. Building construction and operation is the major sources of waste across human activities. Extraction, processing and distribution of materials leads to GHG emission. Excess consumption of material leads to waste generation and consequently GHG emission. Material consumption and waste generation cannot be separated from construction project, building operation and refurbishment. They can only be reduce and their consumption and generation efficiency be increase. Therefore, having appropriate parameters for assessing the distribution and conservation of material is highly important. The study aim at determining the appropriate parameters for material and waste in green building assessment. This can be achieved by consolidating parameters that will universally covers material and waste management in the assessment of sustainable building life cycle. Eleven rating systems and some selected rating tools within them were reviewed. Specifically, the study elaborate on material and waste category and the extent of parameters and points allocation. The study also review the parameters by considering their measurability, preference, prevalence, relevance and adaptability of parameter to suit the universal concept of sustainable building assessment. Material and waste parameters distribution and points allocation show the variability of the rating systems and their tools in assessing the sustainability of their environment. The study consolidated parameters divide the building life cycle in to strategies for conserving material. The other is appropriate waste management during design, construction and operation phase. They also cover estimation of the building carbon footprint from the embodied energy of the material used and waste generated. The other division is the overall carbon footprint reduction during the period of building operation. The study and the parameters can be important in further research activities and to organisations and countries in developing a new rating systems and tools. Through easier distribution of parameters and points allocation to material and waste category.